PARÂMETROS ASSOCIADOS À RESISTÊNCIA AO ÁCARO RAJADO DE GENÓTIPOS DE TOMATEIRO COM ALTOS TEORES DE ZINGIBERENO - Oliveira, João Ronaldo Freitas de (2014)
Since the tomato is a very susceptible plant and is damaged by númerous arthropod pests, one of the major obstacles of Brazilian tomato production is the pest control. As a result, the breeding and the development of cultivars resistant to herbivores has expanded and is indicated as an important strategy in integrated pest management. This study aimed to determine the resistance mechanisms against spider mite that occur in tomato genotypes with high levels of zingiberene. The genotypes were commercially cultivated Redemption (Solanum lycopersicum, low- zingiberene and susceptible to spider mite), the wild Solanum habrochaites var. hirsutum PI- 127826 with high content of zingiberene and resistant spider mite ) , a plant of the F1 generation of interspecific cross (Solanum Redenção x S habrochaites var . hirsutum PI- 127826 ), and three genotypes of the F2 individuals with high levels of zingiberene ( RVTZ pl # 79 ; RVTZ pl # 142 ; RVTZ pl # 331) and two genotypes of the F2 individuals with low- zingiberene levels ( RVTZ pl # 09). To determine the mechanism of resistance, we tested the mites in behavioral free-choice or no-choice bioassays . The density and the category of leaves trichomes on abaxial and adaxial surface were also determined. Genotypes with high zingiberene levels (Solanum habrochaites var hirsutum PI- 127826 , RVTZ pl # 79; RVTZ pl # 142; RVTZ pl # 331 and F1 , were less preferred by the mite to stay and lay eggs in the free-choice bioassays, suggesting that the resistance can be of non-preference type. However, in no-choice bioassays, wild species showed a mortality of nymphs and adult mites. These genotypes also reduced the rate of oviposition in all of bioassays, and prolonged the incubation period of the egg, which achieved 4.8 days in the genotype RVTZ pl # 142. Probably, the antibiosis is also involved in the resistance of these genotypes to the mite. The higher density of type IV and VI glandular trichomes reduced the performance of spider mite in development and oviposition parameters. In this study we observed the association of zingiberene with glandular trichomes, which provided resistance to Tetranychus urticae Koch (Acari: Tetranychidae).